Effect of Modular Distance Learning Approach to Academic Performance in Mathematics of Students in Mindanao State University-Sulu Senior High School Amidst COVID-19 Pandemic - Aksan, Jainalyn Annong (Open Access Indonesia Journal of Social Sciences, 2021)
This study investigated the instructional competencies of teachers in The existence of COVID-19 pandemic brought extraordinary challenges to the stakeholders, teachers, parents, and students. Thus, the researcher believed that there is an effect of teaching-learning process in new normal education to students’ performance most especially using modular type of learning in Mathematics. With this, the study sought to determine the perception of the students regarding modular distance learning approach (MDLA) in Mathematics, identify the challenges of the students, examine the effect of MDLA to academic performance of students in Mathematics, determine the level of academic performance of students, determine the significant difference on perceptions when they grouped according to their gender and age, and determine the relationship of students’ perceptions regarding MDLA to their academic performance in Mathematics. The descriptive research design was utilized in this study. The researcher gathered one hundred seventy eight (178) grade 11 STEM students currently enrolled in MSU-Sulu Senior High School through the use of purposive random sampling. The survey questionnaire was applied in the study. Mean, frequency counts and percentage, t-test for independent samples, one-way analysis of variance (ANOVA), and person product-moment correlation were used to analyze and interpret the data. Based on the result, the study revealed that students’ perceptions agreed on using modular distance learning approach (MDLA). It means the students had positive perceptions regarding MDLA in Mathematics. The study also revealed that students agreed on using modular distance learning approach (MDLA) in Math have little challenges. It had also a positive effect to students’ performance in which students performed very satisfactory in Mathematics which means they had good quality performance. However, the study also revealed that it has no significant difference on their perceptions when they are grouped by gender and age which means the students had the same perceptions.